2010
DOI: 10.1007/s00466-010-0540-y
|View full text |Cite
|
Sign up to set email alerts
|

Ritz analysis of discontinuous beams using local trigonometric functions

Abstract: The objective of the current paper is to present a Ritz-type analytical model for predicting the behavior of discontinuous beams such as thin-walled beams with cracks and multiply-stepped beams. The beam is discretized in the cracked as well as the un-cracked domains for a cracked thinwalled beam and in uniform beams for a multiple-stepped beam. A set of local trigonometric trial functions is used to define the twist angle for the cracked domain and the un-cracked domains, as well as to define the displacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(64 reference statements)
1
4
0
Order By: Relevance
“…The results are shown in Figures 11 and 12. Table 2 shows the comparison of the present results with those obtained by Dang et al [5], with the error calculated using the exact result obtained by Elishakoff et al [6]. A monotonic convergence is observed for all sets under p-refinements.…”
Section: Comparison Of Hierarchical Functions Applied For a Discontin...supporting
confidence: 65%
See 2 more Smart Citations
“…The results are shown in Figures 11 and 12. Table 2 shows the comparison of the present results with those obtained by Dang et al [5], with the error calculated using the exact result obtained by Elishakoff et al [6]. A monotonic convergence is observed for all sets under p-refinements.…”
Section: Comparison Of Hierarchical Functions Applied For a Discontin...supporting
confidence: 65%
“… From Table 2, it is noted that the use of trigonometric functions does not yield results obtained by Dang et al [5]. Although in both the studies, the convergence begins from an upper bound, the frequency obtained by Dang et al is found to go below the exact value.…”
Section: Observations and Conclusionmentioning
confidence: 77%
See 1 more Smart Citation
“…The function used is valid only for cantilever beam and contains multiplied trigonometric and hyperbolic terms that may cause increase of solution time. A set of local trigonometric trial functions, which also contains multiplied trigonometric terms, is employed in the method to determine vibration of multi-stepped Euler–Bernoulli beam (Dang et al., 2011). Bhat (1997) presents variational formulation of the R–R method and investigates the stationarity of the natural frequencies with respect to the arbitrary coefficients of the assumed trigonometric deflection shape of Euler–Bernoulli beams.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al (1999) presents the analyses of models on uniform beams. Most of the works take into account the fundamental beam theory known as ''Euler-Bernoulli beam'' that neglects the effects of rotary inertia and shear deformation (Dang et al, 2011;Janaina and Jose Juliano, 2014;Jaworski and Dowell, 2008;Naguleswaran, 2002Naguleswaran, , 2003Popplewell and Chang, 1996;Pradhan and Chakraverty, 2013;Yamada et al, 1994;Zhou and Cheung, 2000). This theory assumes that energy transmission occurs at the speed approaching infinite for the flexural vibration of thin beams.…”
Section: Introductionmentioning
confidence: 99%